Anxiety level in overweight and obese children - M.L. Aryayev; D.S. Selimkhanova; I.M. Shevchenko (Group of Companies Med Expert, LLC, 2023)
Purpose - to evaluate personal and situational anxiety levels in overweight and obese children. Materials and methods. 153 children (72 girls and 81 boys) aged 12-17 were involved in the study at the Odesa Regional Children's Clinical Hospital. Anthropometric indicators (weight, height, body mass index (BMI)) were assessed taking into account the sex and age of children. Based on BMI values, 3 groups were selected: 1 - children with a body weight corresponding to age and gender - 47 persons (Control); 2 - children with excessive body weight - 50 persons (Overweight); 3 - children with obesity - 56 persons (Obesity). The state of personal and situational anxiety was determined using the Spielberger-Khanin questionnaire. Statistical data analysis was carried out using packages STATISTICA 12.0, MedCalc 20.0, Microsoft EXCEL 2003. Results. In children with obesity, the most common comorbidities were biliary dyskinesia (14.28%), arterial hypertension (10.52%), skin infections 4% and obstructive sleep apnea syndrome 2%. In the studied groups of children, the level of anxiety increased in proportion to the degree of increase in body weight. Personal anxiety in children with obesity compared to control was noted at a higher level - 50.1±1.04 and 30.27±0.98, respectively (χ2=49.9, p=0.0001). Situational anxiety also increased in children with obesity, but the differences were expressed to a lesser extent - 38.94±0.74 and 33.91±0.93 (χ2=5.49, p=0.019). Conclusions. The obtained results indicate the feasibility of further study and monitoring of the psycho-emotional state and quality of life of overweight and obese children and adolescents for individual psychological support and correction of psycho-emotional disorders. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of participating institution. The informed consent of the patient was obtained for conducting the studies. No conflict of interest was declared by the authors.